Derrida’s reading of Merleau-Ponty: to preserve the other from a violent gesture of reappropriation. - Frauenfelder, Raoul (Sapere Aude, 2013)
This article focuses on the relation between Derrida and Merleau-Ponty; in particular, it addresses the role played by “the other” in the constitution of the Self. I reconstruct this relation starting from the critique that Derrida moves to Merleau-Ponty in Le Toucher, which contains Derridas last comparing with phenomenology. Furthermore, the text of Derrida deals with the touch, touching and contact, but also with the touch of the other, following the ambiguity of the French “le toucher”. Haptic experience, as the visual, constitutes the place where Derrida performs the comparison with the Merleau-Pontian treatment of the other. I argue that, by developing the idea of the flesh (la chair), Merleau-Ponty removes the singularity of every single living subject, and I will show that he does it by implementing two gestures. On one hand, he erases the distance in self-contact claiming that the body feels himself without external medium. The subject would be immediate and pure presence of himself, not only in psychic and conscious life, but also in pre-reflexive experience. On the other hand, he compares the self-experience with the experience of the other living and corporeal subject; thus the distinction between the other and me would fall and the other would became just part of me. This is, according to Derrida, a violent gesture of reappropriation of the other; a gesture that fails from the beginning, because it is only oriented by a desire of pure presence. According to Derrida, it is possible to think another history of self and other that subtracts them to the desire of presence to which they are submitted. Actually, the other is always at work, already in the self-experience. I finally show that alterity is the transcendental condition of the experience.